Role of Nanoparticle-Conjugates and Nanotheranostics in Abrogating Oxidative Stress and Ameliorating Neuroinflammation - Tapan A. Patel; Bhavesh D. Kevadiya; Neha Bajwa; Preet Amol Singh; Hong Zheng; Annet Kirabo; Yu-Long Li; Kaushik P. Patel (MDPI AG, 2023)
Oxidative stress is a deteriorating condition that arises due to an imbalance between the reactive oxygen species and the antioxidant system or defense of the body. The key reasons for the development of such conditions are malfunctioning of various cell organelles, such as mitochondria, endoplasmic reticulum, and Golgi complex, as well as physical and mental disturbances. The nervous system has a relatively high utilization of oxygen, thus making it particularly vulnerable to oxidative stress, which eventually leads to neuronal atrophy and death. This advances the development of neuroinflammation and neurodegeneration-associated disorders such as Alzheimer's disease, Parkinson's disease, epilepsy, dementia, and other memory disorders. It is imperative to treat such conditions as early as possible before they worsen and progress to irreversible damage. Oxidative damage can be negated by two mechanisms: improving the cellular defense system or providing exogenous antioxidants. Natural antioxidants can normally handle such oxidative stress, but they have limited efficacy. The valuable features of nanoparticles and/or nanomaterials, in combination with antioxidant features, offer innovative nanotheranostic tools as potential therapeutic modalities. Hence, this review aims to represent novel therapeutic approaches like utilizing nanoparticles with antioxidant properties and nanotheranostics as delivery systems for potential therapeutic applications in various neuroinflammation- and neurodegeneration-associated disease conditions.